1987
DOI: 10.1111/j.1365-3083.1987.tb01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Stimulation with Some Structurally Related Polysaccharides

Abstract: The macrophage-stimulating properties of some structurally related polysaccharides were studied in vitro. When the polysaccharides were presented to the macrophages in a sterically fixed form, i.e. as microparticles, they induced the release of interleukin 1 (IL-1) from the macrophages. Microparticulate 1.3-beta-glucan (curdlan) induced nonspecific macrophage mediated tumour cell killing while 1.4-alpha-glucan (starch), 1.6-alpha-glucan (dextran), and 1.6-alpha-mannan were without effect. The corresponding sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Neovascularization and fibrous septae eventually subdivide CLHAS implants which are then progressively phagocytosed by macrophages [l 11. It is known that macrophages are a key component of the response to implanted CLHAS [lo-121, and that starch has no effect on macrophage nonspecific defense response such as cytotoxic activity [3]. The vacuolated macrophages detected in groups A and D are consistent with phagocytosis of the starch implants.…”
Section: Discussionmentioning
confidence: 54%
“…Neovascularization and fibrous septae eventually subdivide CLHAS implants which are then progressively phagocytosed by macrophages [l 11. It is known that macrophages are a key component of the response to implanted CLHAS [lo-121, and that starch has no effect on macrophage nonspecific defense response such as cytotoxic activity [3]. The vacuolated macrophages detected in groups A and D are consistent with phagocytosis of the starch implants.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, MPH may play a positive role in the wound healing process due to its polysaccharide structure, since MPH is a plantbased polysaccharide. Many studies have shown that polysaccharides accelerate the healing process primarily by macrophage activation (13)(14)(15)(16)(17)(18)(19)(20) as well as by fibroblast stimulation (25)(26)(27) and by T-cell stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…MPH particles form a gelled matrix by concentrating blood solids such as platelets, red blood cells, and blood proteins such as, albumin, thrombin and fibrinogen; thus, are used to achieve hemostasis in case of persistent bleeding (11,12). Also, many studies have shown that polysaccharides accelerate and enhance wound healing via various mechanisms, primarily by increasing the activity of macrophages (13)(14)(15)(16)(17)(18)(19)(20). It can be presumed that the MPH can reduce seroma formation by virtue of these characteristics, by preventing the mechanisms causing seroma formation.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the documented specificity of p-glucan as an activator of macrophages (Seljelid, Bogwald & Lundwall 198 1, Artursson, Edman & Ericsson 1987). While starch particles are avidly phagocytosed by macrophages and starch gels induce peritoneal inflammation, they do not activate macrophages for tumour cell killing (Artursson et al 1987) or leishmanicidal activity (Hoover & Nacy 1984).…”
Section: Discussionmentioning
confidence: 99%